Microstructural and impedance studies of 0.72NBT-0.2ST-0.08KNN ceramic. (2022) - Singha, A.; Praharaj, S.; Rout, D.
Abstract: Lead-free ternary 0.72Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.08K0.5 Na0.5 NbO3 (NBT-ST-KNN) ferroelectric relaxor is prepared by conventional solid state reaction route. The ceramic with dense microstructure is studied by complex impedance spectroscopy over a temperature range from 400 °C to 650 °C. A clear contribution of grain and grain boundaries to the relaxation mechanism is confirmed from the Nyquist plot as a function of frequency and temperature and are investigated using empirical relations. The relaxation time is evaluated from Im Z* plot using Arrhenius law. Existence of two different activation energy values depicts the presence of two different relaxation processes. This investigation on complex impedance and ac conductivity values will provide useful information about the temperature and frequency dependent relaxation and conduction process.